Pediatric Airway Emergency Referrals Requiring Surgical Management: A Five-Year Experience at King Abdulaziz University - Rafat S. Sindi,; Khalil S. Sendi,; Shatha M. Albokhari,; Mahmood A. Alreefi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Pediatric airway emergencies are uncommon, however they are challenging. This study aims to describe our experience in the surgical management of pediatric airway emergencies. This was a retrospective chart review of the medical records of pediatric patients at the Department of Otolaryngology and Head and Neck Surgery of King Abdulaziz University Hospital, between November 2008 and November 2013. We recorded the age, gender, cause of referral, diagnosis, genetic disorders, surgery performed, and the need for further surgical intervention. Data were analyzed using the Statistical Package for the Social Sciences. 37 patients were included with ages between 45 days and 10 years. In most cases, patients were referred for failed extubation, followed by stride; Laryngomalacia was the most frequently diagnosed condition. Less common diagnoses included presence of a thick mucus plug, nearly half of the referred patients had neurological disorders; 40.5% and 27.0% of the patients had respiratory, and cardiovascular disorders, respectively. Bronchoscopy was the most frequently performed surgery, followed by tracheostomy. Less than half of the patients (45.9%) needed further surgical intervention. Pediatric airway emergencies referral is uncommon. Failure to extubate is the most common etiological factor and bronchoscopy is the most commonly performed procedure.